Studies towards the synthesis of himbacine - Parker, J; Parker, Jeremy (1997)
﻿ The natural alkaloid himbacine 1, first isolated in 1955 from Galbulimina baccata Bail, has attracted attention as a potential therapetic agent for Alzheimer's disease. It is proposed that a late stage in the biosynthesis of this compound may proceed via an iminium ion mediated Diels-Alder reaction (Scheme 1), which would yield the related alkaloid himgravine 2, which can be reduced to himbacine 1. Precident for the iminium ion mediated Diels-Alder reaction has been provided by a related oxonium ion mediated cycloaddition reaction (Scheme 2). Confirmation of the stereochemistry of the product of this reaction has been obtained by X-ray crystallography of the tricyclic alcohol. Studies towards the synthesis of the iminium ion have been undertaken. Piperidine sulfone has been synthesised in a 17% yield over 16 linear steps, and a synthesis of dihydrofuran has been investigated involving an enyne metathesis reaction. Additionally, methodology has been developed for a Julia coupling to join piperidine sulfone to dihydrofuran, and a Polonovski reaction for generation of the required iminium ion.